(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
Boko Haram, officially known as Jama’atul Ahlus Sunnah Lidda’wati wal Jihad (People Committed to the Propagation of the Prophet’s Teachings and Jihad), emerged in Borno State, northeastern Nigeria, in 2002. The group’s ideology, centered on rejecting Western education and governance, quickly morphed into violent insurgency. Over time, Boko Haram’s operations expanded into Cameroon, Chad, and Niger, creating a transnational security crisis in the Lake Chad Basin. This study examines the multidimensional factors underlying the group’s rise, persistence, and regional expansion. It argues that a nexus of religious extremism, socioeconomic deprivation, and weak governance has fueled Boko Haram’s growth. Moreover, similar vulnerabilities in neighboring Lake Chad Basin countries have facilitated the group’s transnational reach. Understanding these dynamics is crucial for addressing the systemic conditions enabling the insurgency’s survival.